Anaplastic Lymphoma Kinase Tyrosine Kinase Inhibitor-Associated Cardiotoxicity: A Recent Five-Year Pharmacovigilance Study - Liu, Yihan; Chen, Chen; Rong, Chencheng; He, Xucheng; Chen, Li (Frontiers in Pharmacology, 2022)
Background: Clinical trials frequently reported anaplastic lymphoma kinase tyrosine kinase inhibitors (ALK-TKIs) associated with cardiac adverse drug events (AEs) but minimal postmarketing data. We aimed to research real-world cardiac disorders associated with ALK-TKIs based on the Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Extract reports from the FAERS from the first quarter of 2016 to the second quarter of 2021. Data mining of cardiac disorders associated with ALK-TKIs was carried out by disproportionality analysis to determine the clinical characteristics of AEs. Results: In total, 605 cases were screened out. These events were found to be more prevalent in patients ≥45 years (50.74%) and females (50.74%). The onset of cardiac disorders was variable and concentrated within two months, with a median time of 33 days. The outcomes tended to be poor, with 20.93% fatality proportion. Cardiac arrhythmia is a common adverse event of ALK-TKIs, especially bradycardia. Crizotinib and lorlatinib showed positive signals in cardiac disorders, especially heart failure, and alectinib may be relatively safe for the heart. The study also found that myocarditis caused by ceritinib and cardiomyopathy caused by lorlatinib may be potential new adverse reactions. Conclusion: ALK-TKIs were reported more frequently in cardiotoxicity than other drugs, and could often manifest earlier. We also found potential new AEs signals in specific drugs and need more clinical studies to confirm. Our study helps to fill the safety information of ALK-TKIs in heart and provides directions for further research.